Digital Transformation for Carbon Emission Management as a Strategic Driver for Scope 3 Emission Accountability in the Energy Sector - Fitriastuti, Fransisca; Sunitiyoso, Yos (Yayasan Riset dan Pengembangan Intelektual, 2025)
According to the acceleration of Indonesia’s energy transition and carbon pricing policies, the role of digital transformation in managing carbon emissions is important, especially in addressing Scope 3 emissions, which are still the most complex and indirect (World Bank, 2024). This study explores how the Greenomina platform is implemented by PT Pertamina (Persero) acts as a digitally enabled mechanism for Scope 3 emissions tracking, management, and stakeholder accountability. By applying two frameworks, which are the Digital Transformation Canvas (DTC) and Triple Layer Business Model Canvas (TLBMC), this study identifies critical drivers of ESG integration, employee engagement, and carbon data transparency in PT Pertamina (Persero)’s internal systems (Elia et al., 2024). The findings highlight the transformative potential of corporate innovation in driving to decarbonization strategies while also highlighting persistent barriers such as limited technological infrastructure and digital literacy gaps among internal employee. This study contributes to the growing literature on strategic digitalization for environmental sustainability, offering practical insights for other companies in carbon-intensive sectors, and the pioneer of accountability in carbon emission management. This study aims to become an acceleration of the carbon footprint management for employees, especially in Energy Sector and projected to be implemented by State-Owned Enterprises or Badan Usaha Milik Negara (BUMN) ecosystems in Indonesia.